Delineating the quality and component changes of whole-wheat flour and storage stability of fresh noodles induced by microwave treatment. (October 2017) - Li, Man; Sun, Qing-Jie; Zhu, Ke-Xue
Abstract: In this study, the effects of microwave treatment on the microorganism mortality and PPO activity in whole-wheat flour (WWF) and storage stability of WWF fresh noodles were investigated, as well as the rheological properties of WWF, viscosity and gelatinization properties of starch component, and polymerization and conformational changes of protein. TPC and PPO activity were largely reduced in WWF treated for over 60s. Moreover, it was amazing that microwave treatment significantly increased ( P  < 0.05) dough stability and the resistance to extension. Peak and final viscosity of starch were increased after microwave treatment, with no observable loss of birefringence; SDS-extractable proteins were limitedly decreased and protein aggregating occurred mainly on the large and medium glutenin polymers as shown by the SE–HPLC profiles. In addition, microbial growth and darkening rate of WWF fresh noodles were significantly inhibited, shelf-life of the samples was extended for 3 times after treating for 90 s. Highlights: Microwave treatment largely inhibited the microbial growth and PPO activity in WWF. WWF dough stability and resistance were improved by microwave treatment. Starch viscosity was increased and glutens were limitedly polymerized. Moderate microwave treatment induced no visible starch gelatinization. WWF fresh noodle darkening was significantly reduced and shelf-life was extended.